2009
DOI: 10.1002/ange.200900378
|View full text |Cite
|
Sign up to set email alerts
|

Wachstumsmechanismen Metall‐organischer Gerüststrukturen: Einblicke in die Keimbildung anhand einer schrittweisen Methodik

Abstract: Eins nach dem anderen: Die In‐situ‐Beobachtung der schrittweisen Bildung von Metall‐organischen Gerüstverbindungen (MOFs) mithilfe von Oberflächenplasmonenresonanz ermöglicht mechanistische Studien zur Keimbildung und zur Entstehung sekundärer Baueinheiten sowie Untersuchungen zu den Wachstumsgeschwindigkeiten auf funktionalisierten organischen Oberflächen mit unterschiedlicher kristallographischer Ausrichtung.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0
6

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 34 publications
(52 reference statements)
1
11
0
6
Order By: Relevance
“…[7] Clearly, layer-based PCPs (Figure 2) are structurally more or less related to the Hofmann clathrates and should be particularly suited for LbL growth, since the pronounced anisotropy of this class of PCPs is highly compatible with the boundary conditions dictated by a nucleating, two-dimensional substrate. However, only very few such cases have been reported so far, including [Fe(pz){Pt(CN) 4 }] (pz = pyrazin) [8] and [ZnA C H T U N G T R E N N U N G (bdc)A C H T U N G T R E N N U N G (bipy) 0.5 ] (MOF-508; bdc = 1,4-benzenedicarboxylic acid). [5] This is unfortunate, because layer-based PCPs or MOFs are very promising as novel materials for selective gas sorption and sensing applications.…”
Section: A C H T U N G T R E N N U N G (Btc) 2 -A C H T U N G T R E Nmentioning
confidence: 98%
See 1 more Smart Citation
“…[7] Clearly, layer-based PCPs (Figure 2) are structurally more or less related to the Hofmann clathrates and should be particularly suited for LbL growth, since the pronounced anisotropy of this class of PCPs is highly compatible with the boundary conditions dictated by a nucleating, two-dimensional substrate. However, only very few such cases have been reported so far, including [Fe(pz){Pt(CN) 4 }] (pz = pyrazin) [8] and [ZnA C H T U N G T R E N N U N G (bdc)A C H T U N G T R E N N U N G (bipy) 0.5 ] (MOF-508; bdc = 1,4-benzenedicarboxylic acid). [5] This is unfortunate, because layer-based PCPs or MOFs are very promising as novel materials for selective gas sorption and sensing applications.…”
Section: A C H T U N G T R E N N U N G (Btc) 2 -A C H T U N G T R E Nmentioning
confidence: 98%
“…[3] Later, continuous, extremely smooth, and defect-free multilayer films of HKUST-1 with well-defined thicknesses grown in either the crystallographic [100] or [111] direction were obtained by a self-terminating, liquid-phase, quasi-epitaxial layer-by-layer (LbL) growth process. [4] This LbL fabrication of so-called "SURMOFs" (i.e., surface grown, crystalline metal-organic frameworks) has a number of interesting perspectives. For instance, it allows the control of interpenetration, a phenomenon limiting the pore size when the conventional solvothermal synthesis scheme is employed.…”
Section: A C H T U N G T R E N N U N G (Btc) 2 -A C H T U N G T R E Nmentioning
confidence: 99%
“…[12,13] Several studies have reported on the different stages of the crystallisation process of MOFs with real time studies often providing the greatest information on the processes occurring. [12][13][14][15][16][17][18][19][20][21][22][23][24][25] Atomic force microscopy (AFM) has proved itself as one of the most useful techniques in deciphering the crystal growth process of crystallisation due to its ability to scan surface features with a vertical resolution < 1 and the capacity to perform in situ studies. [20][21][22][26][27][28][29][30][31] In situ AFM studies of dif-Abstract: Crystal growth of the metalorganic framework MOF-5 was studied by atomic force microscopy (AFM) for the first time.…”
Section: Introductionmentioning
confidence: 99%
“…[5] In principle, MOFs crystallized as anisotropic crystallographic systems should exhibit distinct adsorption kinetics for adsorbates approaching from different directions owing to varied pore openings. [10] Thin films of the jungle-gym structured [M 2 (L) 2 (P)] (M = Cu 2+ , Zn 2+ , Co 2+ , Ni 2+ ; L = dicarboxylate, P = dinitrogen pillar ligand) [11] were regulated into [100] and [001] orientations by carboxylate-and pyridyl-terminated SAMs, respectively, on substrates. In contrast, the anisotropic nature of MOF crystals is averaged.…”
mentioning
confidence: 99%